History of Indigenous pharmaceutical companies in colonial Calcutta (1855-1947) - Basu, Malika (Abingdon, Oxon ; New York, NY : Routledge, 2021)
In the context of life and civilization, the pharmaceutical industry is as old as human existence. Since time immemorial India had its own enriched indigenous tradition of medicine. The development of alchemy and its application for human welfare was also an important step in Indian scientific tradition. The present monograph is an innovative attempt to understand the history of the indigenous pharmaceutical companies in Calcutta during the colonial times. Here pharmaceutical companies have been viewed as an illuminating lens to understand the interconnectedness between Indian traditions of thought and Western science and subsequent development of pharmaceutical industry in colonial India. The entire gamut of discussion centres around the issues of medical education, medical services, public health, pharmaceutical profession and politico-economic contexts of the development of pharmaceutical industry in colonial India. Three indigenous pharmaceuticals namely - Butto Krishna Paul & Co., Bengal Chemical & Pharmaceutical Works Limited, and East India Pharmaceutical Works Limited have been studied. The study not only portrays the politico-economic background to the emergence of the pharmaceutical industry in colonial India but links it to the economic nationalism and the quest for self-sufficiency among Indian nationalists and entrepreneurs. The pharmaceutical industry in India can be symbolic of a cultural response to modern science which was to pave the subsequent trajectory of national scientific endeavours in India.Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
OCLC-licensed vendor bibliographic record.
Keywords: Pharmaceutical industry -- India -- Kolkata -- History -- 19th century; Pharmaceutical industry -- India -- Kolkata -- History -- 20th century; Medicine -- India -- Kolkata -- History -- 19th century; Medicine -- India -- Kolkata -- History -- 20th century; India -- History -- British occupation, 1765-1947.